Analysis Of The Application Of 5S And PDCA Methods In The Warehouse Of Speedboat Manufacturing Industry - Adhani, Nurul Indah (Publika Bersama Nusantara, 2025)
PT Komodo Lintas Benua Asia is a speedboat manufacturing company located in Belakang Padang Subdistrict, Batam City. One of the main problems faced by the company is the poor condition of its warehouse, which is disorganized and lacks a proper storage system for production materials. As a result, many materials are found to be damaged or no longer usable, leading to inefficiencies in the production process and increased operational costs. This lack of implementation contributes not only to a messy and inefficient warehouse but also to a lack of employee discipline and accountability. This research was conducted with the aim of addressing these problems through the introduction and application of the 5S methodology. Using the PDCA (Plan-Do-Check-Act) approach, systematic improvements were planned, implemented, monitored, and refined. The results of this study indicate a significant improvement in workplace organization, as shown by the increase in the 5S audit checklist score—from 32% before the intervention to 86% afterward. Among the five pillars of 5S, Seiri and Seiketsu demonstrated the most notable improvement, each showing a score increase from 1 to 5. This indicates that efforts in sorting unnecessary items and standardizing work procedures were particularly effective. The implementation of 5S, supported by the PDCA cycle, has led to a more efficient, cleaner, and safer work environment, while also fostering better discipline and productivity among employees at PT Komodo Lintas Benua Asia.